Hypothesis Relating the Structure, Biochemistry and Function of Active Zone Material Macromolecules at a Neuromuscular Junction - Szule, Joseph A. (Frontiers in Synaptic Neuroscience, 2022)
This report integrates knowledge of in situ macromolecular structures and synaptic protein biochemistry to propose a unified hypothesis for the regulation of certain vesicle trafficking events (i.e. docking, priming, Ca2+-triggering, and membrane fusion) that lead to neurotransmitter secretion from specialized ‘active zones’ of presynaptic axon terminals. Advancements in electron tomography, to image tissue sections in 3D at nanometer-scale resolution, have led to structural and functional characterizations of a network of different classes of macromolecules at the active zone, called ‘Active Zone Material’. At frog neuromuscular junctions, the classes of Active Zone Material macromolecules ‘top-masts’, ‘booms’, ‘spars’, ‘ribs’ and ‘pins’ direct synaptic vesicle docking while ‘pins’, ‘ribs’ and ‘pegs’ regulate priming to influence Ca2+-triggering and membrane fusion. Other classes, ‘beams’, ‘steps’, ‘masts’, and ‘synaptic vesicle luminal filaments’ likely help organize and maintain the structural integrity of active zones. Extensive studies on the biochemistry that regulates secretion have led to comprehensive characterizations of the many conserved proteins universally involved in these trafficking events. Here, a hypothesis including a partial proteomic atlas of Active Zone Material is presented which considers the common roles, binding partners, physical features/structure, and relative positioning in the axon terminal of both the proteins and classes of macromolecules involved in the vesicle trafficking events. The hypothesis designates voltage-gated Ca2+ channels and Ca2+-gated K+ channels to ribs and pegs that are connected to macromolecules that span the presynaptic membrane at the active zone. SNARE proteins (Syntaxin, SNAP25 and Synaptobrevin), SNARE-interacting proteins Synaptotagmin, Munc13, Munc18, Complexin, and NSF are designated to ribs and/or pins. Rab3A and Rabphillin-3A are designated to top-masts and/or booms and/or spars. RIM, Bassoon, and Piccolo are designated to beams, steps, masts, ribs, spars, booms, and top-masts. Spectrin is designated to beams. Lastly, the luminal portions of SV2 are thought to form the bulk of the observed synaptic vesicle luminal filaments. The goal here is to help direct future studies to understand how biochemistry gives rise to Active Zone Material structure, and how it ultimately functions in vivo to regulate the trafficking events that lead to neurotransmitter secretion.